Measurement of Corporate Stock Performance: Case Study in Indonesia and Thailand for the Initial Public Offering (IPO) - Aji Pangestu; Hendro Gunawan; JH Wijaya; Ivan Gumilar Sambas Putra (Trescode Green Organization, 2024)
This study's objective is to compare the performance of company shares in Indonesia and Thailand at the time of their initial public offering (IPO) based on abnormal short-term returns and abnormal long-term returns. This methodology employs descriptive quantitative methods. Population consists of companies in Indonesia and Thailand that conducted an initial public offering (IPO) between 2018 and 2020. Purposive sampling based on predetermined criteria was utilized to obtain samples of 129 companies conducting IPOs in Indonesia and 53 companies conducting IPOs in Thailand. Non-Parametric Difference Mann-Whitney U Test utilizing SPSS version 23.0. The results of the Mann-Whitney U test indicate that there is no statistically significant difference between abnormal returns on short-term (3-month) and long-term stock performance (24 months). significant on the Indonesian and Thai capital markets. Due to the company's poor performance during the period from 2018 to 2020, the stock is underperforming. Obviously, this is demonstrated by the negative abnormal return value. Based on the results of the Mann-Whitney test, it is known that there is no difference between the short-term and long-term stock performance of Indonesian and Thai companies.